Changing Market Relationships in the Internet Age - Jean-Jacques Lambin (Presses universitaires de Louvain, 2008)
This volume, which takes the form of an essay, attempts to structure a forward- looking approach to the evolving role of marketing in today's economy. Many organisations today recognize the need to become more market responsive in view of the growing complexity of the global and interconnected market in which they operate. Internet technology is resulting in an increasingly globalised market, with easier access to information, new market players and new forms of partnerships. It is also chang...